Pengembangan E-Modul Materi Sepak Bola Berbentuk Flipbook pada Sekolah Menengah Pertama (SMP) Kelas IX di SMP Negeri 6 Sukabumi - Fiqri Haidar Ramzy; Bachtiar Bachtiar; Firman Maulana (Jurnal Bintang Pendidikan Indonesia, 2024)
National education aims to develop the potential of students to become individuals who are faithful, devout, have noble character, knowledge and creativity. In this digital era, teachers are required to be innovative, especially in utilizing learning media such as e-modules. At SMP Negeri 6 Sukabumi City, it was found that students had difficulty learning football material and needed additional interactive learning resources, such as flipbook-based e-modules. This research aims to develop, test the validity and measure the practicality of a soccer e-module, as well as observe its impact on student learning motivation. The method used is Research and Development (R&D) with the ADDIE model, which includes the Analyze, Design, Develop, Implement and Evaluate stages. The research was conducted at SMP Negeri 6 Sukabumi City involving 35 class IX students. Data was collected through observation, interviews, questionnaires and documentation. The research results show that the football e-module developed has been assessed as very valid with a percentage of 85% from material experts, 85% from learning experts, and 82.5% from media experts. This e-module is also practical to use in learning, with an increase in practicality from 71% in the first meeting to 80% in the second meeting. This flipbook e-module has proven to be effective in supporting PJOK learning, especially regarding soccer material.